2010
DOI: 10.1016/j.bbrc.2010.04.032
|View full text |Cite
|
Sign up to set email alerts
|

An RNA-hydrolyzing recombinant antibody exhibits an antiviral activity against classical swine fever virus

Abstract: a b s t r a c tSome proteins with ribonuclease (RNase) activity have been shown to suppress viral replication. A wellcharacterized recombinant antibody, 3D8 single-chain variable fragment (3D8 scFv), has RNA-hydrolyzing and cell-penetrating activities. Here, we investigated antiviral activity of 3D8 scFv against classical swine fever virus (CSFV). In a cell line expressing 3D8 scFv (C26), intracellular RNA-hydrolysis activity was higher compared to control PK-15 cells and viral replication was strongly suppres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 20 publications
2
33
0
Order By: Relevance
“…A study recently demonstrated that 3D8 scFv overexpression in HeLa cells following transient transfection was deleterious and resulted in the degradation of the host nucleic acids 18 . However, low levels of 3D8 scFv expression were tolerated by host cells and did not affect the expression of cytoplasmic RNAs including β-actin mRNA and the 28 S and 18 S rRNAs 19 . Using RT-PCR, we demonstrated that the 3D8 scFv gene is expressed in all transgenic chicken organs, and because 3D8 scFv was expressed at low levels and primarily cytoplasmic, cell death was not induced (confocal figure).…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…A study recently demonstrated that 3D8 scFv overexpression in HeLa cells following transient transfection was deleterious and resulted in the degradation of the host nucleic acids 18 . However, low levels of 3D8 scFv expression were tolerated by host cells and did not affect the expression of cytoplasmic RNAs including β-actin mRNA and the 28 S and 18 S rRNAs 19 . Using RT-PCR, we demonstrated that the 3D8 scFv gene is expressed in all transgenic chicken organs, and because 3D8 scFv was expressed at low levels and primarily cytoplasmic, cell death was not induced (confocal figure).…”
Section: Discussionmentioning
confidence: 92%
“…Because the 3D8 scFv protein possesses nuclease activity, 3D8 scFv expression is expected to inhibit viral genome amplification regardless of viral shift and drift 21 , and the 3D8 scFv protein exhibited anti-viral activity against classical swine fever virus (CSFV) in PK15 cells 19 . Therefore, 3D8 scFv overexpression in transgenic chickens is predicted to damage the host genome and induce apoptosis because 3D8 scFv exhibits nuclease activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is noteworthy that m3D8 scFv has anti-viral activity against viruses including classical swine fever virus (CSFV), vesicular stomatitis virus (VSV) (Joung et al, 2012;Jun et al, 2010), and human herpes simplex virus-1 (HSV-1) (Lee et al, 2014). The engineered single domain of 3D8 (3D8 V L ) was able to inhibit the replication of influenza (H9N2) virus (Kim et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…We previously showed that the 3D8 single chain variable fragment (3D8 scFv) nonspecifically binds to and hydrolyzes nucleic acids [12][13][14]. Furthermore, the single variable domains within the heavy and light chains (3D8 VH and VL) efficiently bind and hydrolyze DNA.…”
Section: Introductionmentioning
confidence: 99%